Mother may I? [videorecording (DVD)] - Vannicelli, Laurence; Gaines, Daphne; Gallner, Kyle; Mulkey, Chris (Dark Sky Films, 2023)
Emmett wants to sell his recently deceased mother's house, but lingering memories of childhood abuse soon emerge when he and his fianc ̌Anya stay the night. Anya convinces him to take mushrooms to get him to let go. But something strange happens while they're tripping: she starts behaving like his mother. The next morning, he wakes up sober, but she still won't drop the act. Anya loves playing games, is this her taking it too far? Or did his mother's spirit somehow possess her?